Manipulation of composting oxygen supply to facilitate dissolved organic matter (DOM) accumulation which can enhance maize growth. (June 2021) - Gong, Beini; Zhong, Xiujuan; Chen, Xian; Li, Shikun; Hong, Jiale; Mao, Xiaoyun; Liao, Zongwen
Abstract: Promotion of crop yield by compost application is generally thought to be ascribed to a better supply of macro and micronutrients, however the importance of compost DOM on plant growth has not been well demonstrated. In this study, composting of chicken manure, spent mushroom and sawdust was conducted under aerobic or anaerobic condition to determine the effects of compost DOM on plant growth. It was found that dissolved organic matter (DOM) first increased and then decreased in compost, and DOM of anaerobic compost was slightly higher than that of aerobic compost. When compost extract was applied to maize, among N, P, K and DOM content, it was DOM content that was most significantly and strongly related to plant biomass (r = 0.843, p＜0.001). Compost DOM was also strongly related to soil properties, the improvement of which can also promote plant growth. Compost application confirmed that higher compost DOM results in greater plant biomass. In order to facilitate compost DOM accumulation, we designed a novel composting process which combined aerobic and anaerobic treatments, and the resulting compost (A-Ana compost) with the highest amount of DOM displayed the best performance in promotion of plant growth. A-Ana compost was able to increase maize biomass by 32.71% and 12.40% compared with only anaerobic or aerobic compost, respectively. Therefore, DOM is a critical factor determining compost quality and it is feasible to manipulate composting oxygen supply condition to increase compost DOM, which will lead to increased plant yield. Graphical abstract: Image 1 Highlights: Different composting strategies affect compost DOM. Compost DOM determines the effects of compost on plant growth. Combining aerobic and anaerobic composting facilitates DOM accumulation.